Regulation of plant growth and metabolism by the TOR kinase. (22nd March 2011) - Dobrenel, Thomas; Marchive, Chloé; Sormani, Rodnay; Moreau, Manon; Mozzo, Milena; Montané, Marie-Hélène; Menand, Benoît; Robaglia, Christophe; Meyer, Christian
Abstract : The TOR (target of rapamycin) kinase is present in nearly all eukaryotic organisms and regulates a wealth of biological processes collectively contributing to cell growth. The genome of the model plant Arabidopsis contains a single TOR gene and two RAPTOR (regulatory associated protein of TOR)/ KOG1 (Kontroller of growth 1) and G β L / LST8 (G-protein β-subunit-like/lethal with Sec thirteen 8) genes but, in contrast with other organisms, plants appear to be resistant to rapamycin. Disruption of the RAPTOR1 and TOR genes in Arabidopsis results in an early arrest of embryo development. Plants that overexpress the TOR mRNA accumulate more leaf and root biomass, produce more seeds and are more resistant to stress. Conversely, the down-regulation of TOR by constitutive or inducible RNAi (RNA interference) leads to a reduced organ growth, to an early senescence and to severe transcriptomic and metabolic perturbations, including accumulation of sugars and amino acids. It thus seems that plant growth is correlated to the level of TOR expression. We have also investigated the effect of reduced TOR expression on tissue organization and cell division. We suggest that, like in other eukaryotes, the plant TOR kinase could be one of the main contributors to the link between environmental cues and growth processes.